Complete Heart Block Caused by Diffuse Pseudotumoral Cardiac Involvement in Granulomatosis With Polyangiitis. Issue 17 (27th October 2015) - Colin, Geoffrey C.; Vancraeynest, David; Hoton, Delphine; Jonard, Paul; Gerber, Bernhard
Abstract : Supplemental Digital Content is available in the text.